Estimation of Glomerular Filtration Rate Based on Serum Cystatin C versus Creatinine in a Uruguayan Population - Inés Lujambio; Mariana Sottolano; Leonella Luzardo; Sebastián Robaina; Nadia Krul; Lutgarde Thijs; Florencia Carusso; Alicia da Rosa; Ana Carina Ríos; Alicia Olascoaga; Mariela Garau; Liliana Gadola; et al. (International Journal of Nephrology)
Background. Estimation of glomerular filtration rate (eGFR) from biomarkers has evolved and multiple equations are available to estimate renal function at bedside. Methods. In a random sample of 119 Uruguayans (54.5% women; 56.2 years (mean)), we used Bland and Altman’s method and Cohen’s kappa statistic to assess concordance on a continuous or categorical (eGFR < 60 versus ≥60 mL/min/1.73 m2) scale between eGFRcys (reference) and eGFR derived from serum creatinine according to the Modification of Diet in Renal Disease (eGFRmdrd) or the Chronic Kidney Disease Epidemiology Collaboration equations (eGFRepi) or from both serum cystatin C and creatinine (eGFRmix). Results. In all participants, eGFRmdrd, eGFRepi, and eGFRmix were, respectively, 9.7, 11.5, and 5.6 mL/min/1.73 m2 higher (P<0.0001) than eGFRcys. The prevalence of eGFR <60 mL/min/1.73 m2 was the highest for eGFRcys (21.8%), intermediate for eGFRmix (11.8%), and the lowest for eGFRmdrd (5.9%) and eGFRepi (3.4%). Using eGFRcys as reference, we found only fair agreement with the equations based on creatinine (Cohen’s kappa statistic 0.15 to 0.23). Conclusion. Using different equations we reached clinically significant differences in the estimation of renal function. eGFRcys provides lower estimates, resulting in higher prevalence of eGFR <60 mL/min/1.73 m2.